PCOSKB(R2): a database of genes, diseases, pathways, and networks associated with polycystic ovary syndrome - Sharma, Mridula (Sci Rep, 2020)
PolyCystic Ovary Syndrome KnowledgeBase (PCOSKB(R2)) is a manually curated database with information on 533 genes, 145 SNPs, 29 miRNAs, 1,150 pathways, and 1,237 diseases associated with PCOS. This data has been retrieved based on evidence gleaned by critically reviewing literature and related records available for PCOS in databases such as KEGG, DisGeNET, OMIM, GO, Reactome, STRING, and dbSNP. Since PCOS is associated with multiple genes and comorbidities, data mining algorithms for comorbidity prediction and identification of enriched pathways and hub genes are integrated in PCOSKB(R2), making it an ideal research platform for PCOS. PCOSKB(R2) is freely accessible at http://www.pcoskb.bicnirrh.res.in/.